An assessment of business intelligence in public hospitals - Rikke Gaardboe; Niels Sandalgaard; Tom Nyvang (International Journal of Information Systems and Project Management, 2017)

(untitled)
In this paper, DeLone and McLean's information systems success model is empirically tested on 12 public hospitals in Denmark. The study aims to investigate the factors that contribute to business intelligence (BI) success. 1,352 BI end-users answered the questionnaire. A partial least square structural equation model was used to empirically test the model. We find that system quality is positively and significantly associated with use and user satisfaction, and that information quality is positively and significantly associated with user satisfaction. User satisfaction is positively and significantly related to individual impact. The other paths in the model are insignificant. Our findings also provide empirical support for the role of user satisfaction as a mechanism that mediates the relationship between information quality or system quality and individual impact. User satisfaction is not only a critical construct in the information systems success model but it also serves as a mediator. Generally, the model finds empirical support, as it has a good fit and predictive value.